1985
DOI: 10.1044/jshr.2804.505
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic Inventories, 15–24 Months

Abstract: Longitudinal samples of meaningful speech of 34 normally developing children were analyzed to determine the range and types of consonantal phones produced at 15, 18, 21, and 24 months. Separate inventories for word-initial and word-final consonants were constructed for each child at each age level. Group analyses showed that early inventories in initial position were composed primarily of voiced anterior stops, nasals, and glides; by 24 months, voiceless stops, velars, and a few fricatives were also included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
183
2
14

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(219 citation statements)
references
References 0 publications
20
183
2
14
Order By: Relevance
“…For each word, the independent and relational age of acquisition was determined for both the initial and final consonant. For the independent age of acquisition, the earliest age when 50% of 15-to 39-month-old children's phonetic inventories included the sound was determined from Stoel-Gammon (1985) and Dyson (1988). For the relational age of acquisition, the proportion of 3-year old children who correctly articulated each consonant was obtained from the data by Smit, et al (1990).…”
Section: Variablesmentioning
confidence: 99%
“…For each word, the independent and relational age of acquisition was determined for both the initial and final consonant. For the independent age of acquisition, the earliest age when 50% of 15-to 39-month-old children's phonetic inventories included the sound was determined from Stoel-Gammon (1985) and Dyson (1988). For the relational age of acquisition, the proportion of 3-year old children who correctly articulated each consonant was obtained from the data by Smit, et al (1990).…”
Section: Variablesmentioning
confidence: 99%
“…Number of phones in the final position ranged from 0 to 2. These inventory sizes are comparable to those of typically developing, US-born young children (Stoel-Gammon, 1985). Stoel-Gammon reported that at 15 months of age, the number of different consonants in the initial position ranged from 2-5, with a mean of 3.4 consonants.…”
Section: Six Months Post-adoptionmentioning
confidence: 48%
“…The internationally adopted children's final consonant inventories were also similar to those of US-born children (Stoel-Gammon, 1985). The 16 month olds, S2 and S3, produced 1 and 0 final consonants, respectively.…”
Section: Six Months Post-adoptionmentioning
confidence: 55%
See 1 more Smart Citation
“…Los resultados de este estudio muestran una prevalencia de AC (53%), que es mayor a la de El inventario de sílaba-consonante canónica que tenga el menor, predice el inventario de la palabraconsonante inicial posterior 37 . En los niños con fisura sin reparar, el balbuceo canónico se puede ver afectado, ya que interferiría en el desarrollo apropiado de las habilidades oromotoras de control, que le permiten al bebé comenzar a producir sílabas canónicas 38,39 .…”
Section: Discussionunclassified